GROWING TOMATOES BY USING ORGANIC FARMING METHODS IN PRIVATE SECTOR OF THE FOREST-STEPPE OF UKRAINE - Chaika, T. O.; Barabolia, O. V.; Perepadchenko, T. O. (Scientific Progress & Innovations, 2021)
Receiving high yields of tomatoes must not take place at the expense of decreasing their safety for human health, but on the contrary, it is the necessary precondition of using organic farming methods for their cultivation. As on the country’s scale it still cannot be achieved, however it is possible to take care of tomatoes’ environmental safety on private farms. Connected with the set purpose, the effectiveness of tomato cultivation in the village of Zachepylivka (Novi Sanzhary district, Poltava region) was considered. The methods of using organic farming methods in the private sector were studied taking into account tomato variety properties of early-ripening Etiud, Lada, Asteroid varieties and late-ripening Tytan variety. To improve the sowing qualities of tomato seeds, stimulate growth processes, increase plant stress-resistance, seed disinfection from pathogenic microorganisms, we conducted pre-sowing seed treatment with UV irradiation using ZW20D15W lamp type of 20 w capacity. Tomato seeds were sown in peat-manure pots, and VERMICONTM bio-humus was added in soil mixture, 20 % from the total weight. Taking into account cool spring, in order to increase cold endurance of tomato seedlings, their hardening was conducted. While planting tomatoes, considerable attention was paid to crop rotation, and seedlings were planted after cucumbers and onions, and farther away from potatoes in order to decrease the threat of blight infection. Low varieties (Tytan, Asteroid) were planted by wide-row method with 60 cm space between the rows and 30–40 cm in the rows. Higher tomato varieties (Etiud, Lada) were placed by 50x60 cm scheme. The studies of biometric indices of the above mentioned varieties after two months have shown that plants of Lada tomato variety are characterized by the largest height of the main stem, which corresponds to their variety peculiarities. The sufficient amount of moisture in the soil favored the growth of tomato shrubs of Asteroid and Tytan varieties 20 and 13 cm higher than their variety characteristics respectively. The stems are thicker in Tytan and Etiud varieties. Etiud and Tytan varieties have the longest leaf length (12 and 11 cm, respectively), while Lada and Asteroid varieties have equal leaf length (9 cm). Etiud, Tytan, and Asteroid varieties have the widest leaves. The studies of tomato yield potential have shown that Etiud variety has the largest number of tomatoes however they are not big by diameter and weight. Asteroid variety is characterized by the smallest number of tomatoes and sizes among other varieties, while Lada variety has by 40% more tomatoes and they are bigger than in other varieties. Thus, the following tomato varieties are the most suitable and high-yielding for cultivating by organic farming methods in the private sector of the Forest-Steppe of Ukraine: early-ripening Lada and Etiud varieties and late-ripening Tytan variety.